(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Fermented foods have made important contributions to human diets for thousands of years and continue to do so. Their health-promoting benefits are attracting increasingly attention. The present study was conducted to evaluate the impact of natural fermentation on antioxidant properties of traditionally fermented wheat (Triticum durum) compared to unfermented samples. Initially, the samples were submitted to traditional spontaneous fermentation. Subsequently, an aqueous extract was obtained and used to determine polyphenolic and flavonoid contents. Moreover, the antioxidant potential was also measured through the determination of the scavenging ability against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals, reducing power and hydrogen peroxide scavenging activity. The results showed that the total phenolic and total flavonoid contents were significantly increased in fermented wheat. Moreover, the antioxidant activity was more effective in fermented than in unfermented wheat. Thus, natural fermentation can enhance natural antioxidants in wheat and transform it into a healthy food or ingredient with multi-functional properties which can be used in the food industry.